Sosialisasi dan Pendampingan Pembuatan Laporan Keuangan Pada Peternak Ayam Boiler di Desa Kawo Kabupaten Lombok Tengah: Socialization and Assistance in Making Financial Reports on Boiler Chicken Farmers in Kawo Village, Central Lombok Regency - Mandalika, Eka Nurminda Dewi; Anna Apriana Hidayanti; Rifani Nur Sindy Setiawan; Ni Made Nike Zeamita Widiyanthi; Sharfina Nabilah (Universitas Mataram, 2025)
This service activity was carried out in Kawo Village involving 15 broiler farmers. This activity has several objectives including: (1) increasing the understanding of broiler farmers in Kawo Village about the importance of financial recording and reporting; (2) providing training and socialization on simple financial reports; (3) assisting farmers in preparing financial reports directly; (4) building awareness and good habits in financial administration for business efficiency and access to funding. The steps taken in this service activity include: Initial Survey and Problem Identification, Socialization and Education, Technical Training, Individual Assistance and Evaluation and Follow-up. The results of the service showed several positive findings. First, there is an increase in farmers' knowledge about the importance of financial recording and reporting in the broiler farming business. Second, farmers began to familiarize themselves with recording finances regularly, either daily, weekly or monthly. Third, they were able to prepare simple financial reports that included records of income, expenses, profit/loss and cash flow. Finally, farmers can make better business decisions based on accurate and structured financial information.